Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/su14105786
|View full text |Cite
|
Sign up to set email alerts
|

Public Awareness of Nanotechnology and Its Implications for Health in Jordan

Abstract: Nanotechnology is often described as an emerging technology, holding promise for a diverse range of fields. Public awareness may have a strong impact on public acceptance of nano-technology and its various implications. In Jordan, nano-education has only been introduced recently into universities and it is offered to students of pharmacy, engineering, biomedical sciences, and agriculture. However, there is no data available on nanotechnology awareness among the public in Jordan. Therefore, we conducted this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Consumer perception, acceptance and knowledge of nanotechnology ( Cummings et al, 2021 ) may also be an impediment to food application. The majority of respondents (67%) indicated that they had little knowledge and understanding of nanotechnology, nanomaterials, and nanoproducts, and about 42% responded they had little understanding of its effects on food ( Arabeyyat, Jamaliah & Khalaf, 2022 ). Due to this low level of awareness, consumers are unable to make an informed evaluation of the potential risks to health and the environment ( Ummi & Siddiquee, 2019 ).…”
Section: Challenges With Nano-delivery Methodsmentioning
confidence: 99%
“…Consumer perception, acceptance and knowledge of nanotechnology ( Cummings et al, 2021 ) may also be an impediment to food application. The majority of respondents (67%) indicated that they had little knowledge and understanding of nanotechnology, nanomaterials, and nanoproducts, and about 42% responded they had little understanding of its effects on food ( Arabeyyat, Jamaliah & Khalaf, 2022 ). Due to this low level of awareness, consumers are unable to make an informed evaluation of the potential risks to health and the environment ( Ummi & Siddiquee, 2019 ).…”
Section: Challenges With Nano-delivery Methodsmentioning
confidence: 99%
“…The core text Acquiring a deep understanding of complex and controversial scientific concepts requires the reconstruction of intuitive notions to create a more robust scientific conceptual framework (Arabeyyat et al, 2022). The chemistry education faces the challenge of ensuring that students fully grasp the concepts that are being presented to them (Song & Long, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Further, before and after the instructional tools, an achievement test based on nanotechnology and classification of nonmaterial was conducted, covering all six cognitive domains of the Bloom taxonomy of educational objectives. Data analysis revealed that the instructional tools based on constructivist approach had a statistically Introduction Acquiring a deep understanding of complex and controversial scientific concepts like atomic structure, space-time curvature and nanotechnology, require the reconstruction of intuitive notions to create a more robust scientific conceptual framework (Arabeyyat et al, 2022). The chemistry and physics education faces the challenge of ensuring that students fully grasp the concepts of nanotechnology that are being presented to them (Song and Long, 2022).…”
mentioning
confidence: 99%